Pharmacological inhibition of the MAP2K7 kinase in human disease - Lacorazza, H. Daniel (Frontiers in Oncology, 2024)
The MAP2K7 signaling pathway activates the c-Jun NH2-terminal protein kinase (JNK) in response to stress signals, such as inflammatory cytokines, osmotic stress, or genomic damage. While there has been interest in inhibiting JNK due to its involvement in inflammatory processes and cancer, there is increasing focus on developing MAP2K7 inhibitors to enhance specificity when MAP2K7 activation is associated with disease progression. Despite some progress, further research is needed to fully comprehend the role of MAP2K7 in cancer and assess the potential use of kinase inhibitors in cancer therapy. This review examines the role of MAP2K7 in cancer and the development of small-molecule inhibitors.